Additional information on the taxonomy of genus Asclerobia Roesler, 1969 (Lepidoptera; Pyralidae) - Yepishin, Viktor (Zootaxa, 2023)
The current contribution aims to supplement a previous one by the author (2021) with information on new taxonomic changes in the systematics of genus Asclerobia, and to correct some diagnosis errors. Two new species-group taxa are established as synonyms: Asclerobia flavitinctella (Ragonot, 1893) = Salebria tchahabarella Amsel, 1950 syn. nov., and Asclerobia sinensis (Caradja in Caradja & Meyrick, 1937) = Etiella yangtseella Caradja, 1939 syn. nov. The hitherto unknown female genitalia of Asclerobia flavitinctella are described, and the improved diagnosis of this species as well as Asclerobia sinensis are given. The updated keys based on external features and genitalia of both sexes, as well as a revised distribution map for Asclerobia species are provided.